Phase Diagram and Thermodynamic Properties of Ketoprofen-Succinic Acid Binary Mixtures - Wicaksono, Yudi; Setyawan, Dwi; Siswandono, S. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
The equilibrium phase diagram and thermodynamic properties of a mixture of drugs and additives are information related to various possible interaction processes between components. Therefore, we conducted a study of the phase diagrams and thermodynamic properties of binary mixtures of ketoprofen-succinic acid to estimate the types of interactions that may occur between these materials. The solid-liquid phase diagram of ketoprofen-succinic acid binary mixtures was determined by differential scanning calorimetry and composition of eutectic system was determined accurately using a Tamman diagram. The measurement of binary mixtures of ketoprofen-succinic acid with differential scanning calorimeter obtained the value of melting temperature and heat of fusion of ketoprofen- succinic acid system. The solid-liquid phase diagram of ketoprofen- succinic acid showed the formation of eutectic type phase diagram. The Tamman diagram showed accurately composition of the eutectic system of the Kp-SA binary mixtures at the mole fraction of Kp 0.87 and temperature 96.9oC.Keywords: ketoprofen, phase diagram, eutectic system, Tamman diagram